Classroom lighting design for students with autism spectrum disorders - Long, Emily Ann (Kansas State University, 2010)
Autism Spectrum Disorders, (ASD) are being diagnosed at an alarming rate. Students with ASD face many challenges in educational environments and struggle to overcome daily distractions. Students with ASD have variances in neuron connections that cause them to receive and understand their environment differently than a student without special needs. In the educational classrooms, fluorescent lighting is a significant source of extraneous stimuli that not only a source of annoyance but can also trigger common symptoms of ASD. Fluorescent fixtures economically provide an acceptable uniformity and quality of illumination, but also have disadvantages that can aggravate symptoms in students with ASD. Ballasts are required for the operation of fluorescent fixtures. These ballasts, especially if not replaced at the end of their usable life, can generate an audible hum and cyclical flickering of light. Alternative light sources, such as incandescent lamps and fixtures should be evaluated and installed not only in special needs classrooms but standard group classrooms as well. Providing additional sources or quality sources of light may help students with ASD focus on the information presented in the classroom. Traditional classroom design needs to be re-evaluated to accommodate the needs of those students with ASD to better provide a comfortable and less distracting learning environment. It is difficult to establish rigid standards for lighting designs sensitive to individuals and special needs occupants'. By understanding the symptoms of ASD and taking into account the occupants needs lighting designers will be better able to design an environment that is both comfortable and educational. This report will address the classroom environment and student considerations in order to develop parameters and design practices that will assist new lighting designers.
Keywords: Autism; Fluorescent; Lighting; Incandescent; Flicker; Engineering, Electronics and Electrical (0544); Health Sciences, Education (0350)